LEGENDA GOA PUTRI DAN SI PAHIT LIDAH DESA PADANG BINDU: TINJAUAN STRUKTURALISME LEVI-STRAUSS - Sariasih, Yanti; Rita Nilawijaya (Literasi: Jurnal Ilmiah Pendidikan Bahasa, Sastra Indonesia dan Daerah, 2024)
This research aims to examine the structure of the legend of Goa Putri and Si Pahit Lidah in the Padang Bindu area, Ogan Komering Ulu Regency, South Sumatra. The research method uses a qualitative descriptive method combined with Levi-Strauss's Structuralism theory. Data mining techniques were carried out using interview, observation and documentation techniques. The results of this research show that there are four episodes of the Legend of Goa Putri and Si Pahit Lidah, namely (1) the initial episode and the origins of Putri Dayang Merindu, (2) episodes of the characters' lives and daily lives, (3) problem episodes, and (4) final episodes. There are four myths in the Legend of Goa Putri and Si Pahit Lidah, namely (1) the myth of the tiger guarding Goa Putri, the friend of Princess Dayang Merindu, (2) the myth of Sumuhun water which can make you stay young, (3) the myth of Si Pahit Lidah's curse on Princess Dayang Merindu, and (4) the myth of the curse of the Si Pahit Lidah for the village area. There are three forms of binary opposition relations, namely relations of differences in status between characters, relations of place, and relations of differences in time. The values contained are (1) friendship can be made with anyone, (2) an invitation to love the environment, especially water, maintaining the sustainability, cleanliness and clarity of water as a source of life for humans and other living creatures, and (3) teaching humans to be able to hold back anger or be patient and be kind to anyone. Keywords: Legend, Goa Putri, The Bitter Tongue, Levi-Strauss Structuralism